Vitreous - Sebag, J. (Henry Stewart Talks, 2016)
Vitreous structure & biochemistry, Formation of the vitreous, Age-related macular degeneration, Vitreous & the vitreo-retinal interface, Posterior vitreous detachment (PVD), Surgical strategies for retinal detachment (RD), Vitreo-maculopathies: Macular hole & macular pucker, Pharmacologic vitreolysis